2023
DOI: 10.1002/icd.2409
|View full text |Cite
|
Sign up to set email alerts
|

Peer ethnic/racial socialization in adolescence: Current knowledge and future directions

Abstract: Peer groups are a central socialization setting in adolescence, and an emerging body of research has started to investigate the influence of peers on how adolescents understand, think about, and act on issues of ethnicity and race. This commentary summarizes the existing research that has investigated peer ethnic/racial socialization (ERS) and its associations with adolescent outcomes, highlighting the need to better understand: (1) what peers are doing related to issues of ethnicity/race; (2) who these peers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous literature highlights the utility of college students as agents of racial socialization as they process and communicate racial messages, practices, values, and experiences (Barr & Neville, 2014;Golden et al, 2022;Hughes et al, 2011;Nelson et al, 2018). Furthermore, some studies have suggested that PRS is linked to an increase in Black adolescents and emerging adults' (including college students) sense of self, psychological adjustment, sociopolitical development, and coping with racial discrimination (Wang & Lin, 2023). However, few studies have considered the role of increasingly ubiquitous digital landscapes as a critical context for Black adolescents and emerging adults to exchange racial socialization messages with Black peers (Ruck et al, 2021;Sladek et al, 2022) despite the established normality of digital media in the lives of Black youth (Lenhart et al, 2015).…”
Section: The Present Studymentioning
confidence: 99%
“…Previous literature highlights the utility of college students as agents of racial socialization as they process and communicate racial messages, practices, values, and experiences (Barr & Neville, 2014;Golden et al, 2022;Hughes et al, 2011;Nelson et al, 2018). Furthermore, some studies have suggested that PRS is linked to an increase in Black adolescents and emerging adults' (including college students) sense of self, psychological adjustment, sociopolitical development, and coping with racial discrimination (Wang & Lin, 2023). However, few studies have considered the role of increasingly ubiquitous digital landscapes as a critical context for Black adolescents and emerging adults to exchange racial socialization messages with Black peers (Ruck et al, 2021;Sladek et al, 2022) despite the established normality of digital media in the lives of Black youth (Lenhart et al, 2015).…”
Section: The Present Studymentioning
confidence: 99%
“…A growing body of research suggests that peers also communicate messages regarding race and racism to each other, highlighting peers as a potential source of children's racial learning and knowledge (Wang & Lin 2023). Peers become increasingly important for well-being and selfperception during middle childhood and adolescence: Peer norms, peer ideas, peer acceptance, and peer support are critically important for youths' well-being and positive adaptation.…”
Section: Peers As Sources Of Youths' Racial Learning and Knowledgementioning
confidence: 99%
“…Peer racial socialization occurs in the course of youths' everyday interactions but is distinct from parental racial socialization in several ways (Wang & Lin 2023). It occurs across multiple settings, including classrooms, lunchrooms, baseball fields, and extracurricular activities; it occurs in multiple forms that may not be deliberate or constructive; and it can occur from cross-race and same-race individuals.…”
Section: Summary Of Peer Racial Socializationmentioning
confidence: 99%